Anti-IL-5 attenuates activation and surface density of β(2)-integrins on circulating eosinophils after segmental antigen challenge - Johansson, Mats W. (2013)
BACKGROUND: IL-5 activates α(M)β(2) integrin on blood eosinophils in vitro. Eosinophils in bronchoalveolar lavage (BAL) following segmental antigen challenge have activated β(2)-integrins. OBJECTIVE: To identify roles for IL-5 in regulating human eosinophil integrins in vivo. METHODS: Blood and BAL eosinophils were analyzed by flow cytometry in ten subjects with allergic asthma who underwent a segmental antigen challenge protocol before and after anti-IL-5 administration. RESULTS: Blood eosinophil reactivity with monoclonal antibody (mAb) KIM-127, which recognizes partially activated β(2)-integrins, was decreased after anti-IL-5. Before anti-IL-5, surface densities of blood eosinophil β(2), α(M), and α(L) integrin subunits increased modestly post-challenge. After anti-IL-5, such increases did not occur. Before or after anti-IL-5, surface densities of β(2),α(M), α(L), and α(D) and reactivity with KIM-127 and mAb CBRM1/5, which recognizes high-activity α(M)β(2), were similarly high on BAL eosinophils 48 h post-challenge. Density and activation state of β(1)-integrins on blood and BAL eosinophils were not impacted by anti-IL-5, even though anti-IL-5 ablated a modest post-challenge increase on blood or BAL eosinophils of P-selectin glycoprotein ligand-1 (PSGL-1), a receptor for P-selectin that causes activation of β(1)-integrins. Forward scatter of blood eosinophils post-challenge was less heterogeneous and on the average decreased after anti-IL-5; however, anti-IL-5 had no effect on the decreased forward scatter of eosinophils in post-challenge BAL compared to eosinophils in blood. Blood eosinophil KIM-127 reactivity at the time of challenge correlated with the percentage of eosinophils in BAL post-challenge. CONCLUSION AND CLINICAL RELEVANCE: IL-5 supports a heterogeneous population of circulating eosinophils with partially activated β(2)-integrins and is responsible for upregulation of β(2)-integrins and PSGL-1 on circulating eosinophils following segmental antigen challenge but has minimal effects on properties of eosinophils in BAL. Dampening of β(2)-integrin function of eosinophils in transit to inflamed airway may contribute to the decrease in lung inflammation caused by anti-IL-5.